Fakor-Faktor yang Mempengaruhi Permintaan Buah Salak Bali (Salacca Zalacca var. ambonensi) oleh Rumah Tanggadi Kota Denpasar, Provinsi Bali - MEDIKANA, I NENGAH ARI; SUDARMA, I MADE; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Factors that Affect to Demand of Salak Bali Fruit (Salacca Zalacca var. ambonensi) by Householdin Denpasar City,Bali Province T his study aims to know factors that affectdemand quantity ofSalak Bali fruit and magnitude the elasticity of Salak Bali fruit ’s demand in Denpasar City. L ocation of study was atBadung Market, Kreneng Market, Sanglah Market, and Satrya Market that has been determinated purposive ly . P opulationswas houshold which bought Salak Bali fruit attraditional markets . This study used accidental samplingtechnique.There were 40 samples which has been determined purposively . This study used thetransformed multiple regressionf unction model . Independen t variables are X 1 ( price of Salak Bali fruit ) , X 2 ( price of orange ) , X 3 ( price of apple ) , X 4 ( price of mango ) , X 5 ( quantity of household members ) , X 6 ( income of household ) , and dummy (t here are religious celebrations/there aren’t any religious celebrations). The function model is LNY = 2,65 - 1,126 LNX 1 ** - 1,360 LNX 2 ** - 0,643 LNX 3 ** + 0,892LNX 4 * + 0,363LNX 5 ** + 0,590LNX 6 ** + 0.129D ** . Factors that affectdemand quantity of Salak Bali fruit are price of Salak Bali fruit, price of orange, price of apple, price of mango, quantity of household members, income household, and situasion. The price e lasitcity is elastis, based on cross elasticity both orange and apple are complementary product, while mango is substitution product of Salak Bali fruit. The i ncome elasticity show s that Salak Bali fruits is normal product. K eywords : demand , Salak Bali fru i t , Denpasar City , elasticity